FACTOR-FACTOR THAT INFLUENCING INDEPENDENCE OF PUBLIC-SECTOR AUDITOR: A LITERATURE REVIEW - Doan, Vu Anh; Nguyen, Hung Xuan (School of Accountancy, University of Agung Podomoro, 2023)
The study of public sector audit is a relatively large, complex, unexplored and underrecognizedfield. Therefore, researchers call for more studies on public sector audit, especially in thecontext of developing countries. This article gives review of academic study pertaining to public-sectorauditors’ independence and factors affecting public-sector auditors’ independence. This literaturereview is implemented based on published papers in 20th century in prestigious journals related topublic sector audit. Firstly, we review and explain definition of independence clearly. Secondly, weorganize our review around three main threats to public-sector auditors’ independence, namely, (a)political manifestos, (b) auditor tenure, and (c) relationship with auditee. For each of the threats, thisstudy discusses the effects of each threat on the public-sector auditors’ independence. Additionally, weconclude that proofs together with recent changes, provides for future study on public-sector auditor’sindependence.